2015
DOI: 10.2903/j.efsa.2015.3981
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety of the change in the production method of L-glutamic acid (E620), monosodium L-glutamate (E621), monopotassium L-glutamate (E622), calcium di-L-glutamate (E623), monoammonium L-glutamate (E624) and magnesium di-L-glutamate

Abstract: European Food Safety Authority (EFSA), Parma, Italy ABSTRACTThe Panel on Food Additives and Nutrient Sources added to Food (ANS) was asked to deliver a scientific opinion evaluating the safety of the change in the production method for the production of L-glutamic acidThe L-glutamic acid is produced by the genetically modified Corynebacterium glutamicum EA-12 strain. The recipient strain Corynebacterium glutamicum strain 2256 has been recommended for Qualified Presumption of Safety (QPS) status. No antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…L-Glutamic acid may be converted to the monosodium salt by the addition of sodium hydroxide (Sano, 2009). EFSA evaluated a process for the production of L-glutamic acid produced by fermentation using the genetically modified C. glutamicum EA-12 strain obtained from strain 2256 (EFSA ANS Panel, 2015). The modified strain produces L-glutamic acid more efficiently compared to the 'standard' biosynthetic/ metabolic pathway present in C. glutamicum described above.…”
Section: Manufacturing Processmentioning
confidence: 99%
See 2 more Smart Citations
“…L-Glutamic acid may be converted to the monosodium salt by the addition of sodium hydroxide (Sano, 2009). EFSA evaluated a process for the production of L-glutamic acid produced by fermentation using the genetically modified C. glutamicum EA-12 strain obtained from strain 2256 (EFSA ANS Panel, 2015). The modified strain produces L-glutamic acid more efficiently compared to the 'standard' biosynthetic/ metabolic pathway present in C. glutamicum described above.…”
Section: Manufacturing Processmentioning
confidence: 99%
“…In the processes described above, glutamic acid is produced by fed-batch fermentation using carbon sources of vegetal origin (sucrose), nitrogen sources, salts and vitamins. According to the new manufacturing process (EFSA ANS Panel, 2015), there are no differences in the qualitative composition of the medium between the new and the conventional process except that the quantity of the raw materials used have been adapted, due to the particularity of the new strain.…”
Section: Manufacturing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…MSG was once believed to cause side effects, such as headache and nausea. However, studies have found no consistent clinical data to support these claims (International Glutamate Information Service, 2022a , 2022b ; Maluly et al, 2017 ) and the safety of MSG has been approved by official agencies worldwide, including those in Europe (EFSA Panel on Food additives and Nutrient Sources added to Food, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The industrial production of potassium glutamate is by the neutralization of glutamate. 7 As shown in Scheme 1, 8 the glutamate crystal purified by fermentation is neutralized by adding potassium hydroxide, where the pH, temperature, concentration, and other conditions are adjusted to make it completely dissolved. After complete dissolution, activated carbon is added to absorb colored impurities, and then a mineral agent is added to filter it.…”
Section: ■ Introductionmentioning
confidence: 99%